NEUROTICISM, COPING AND CHRONIC PAIN - Ramírez Maestre, Carmen; Esteve Zarazaga, Rosa; López Martínez, Alicia Eva (Anales de Psicología / Annals of Psychology, 2001)
This study aims mainly to collate the various hypotheses on the relationship between the levels of neuroticism, the intensity of experienced pain and the coping strategies used by patients with chronic pain. In order to achieve that, we used a sample of 100 patients with chronic pain, either benign or oncologic, who come to the Pain Unit and to the Rheumatology Service of the Residencia Hospitalaria Carlos Haya in Málaga. The assessment tools used are: Vanderbilt Pain Management Inventory (Brown and Nicassio, 1987); Spanish Version of Pain McGill Questionnaire (Ruiz et al., 1990) and Spanish Version of Eysenck Personality Inventory (Eysenck and Eysenck, 1990). The hypothetical model developed has been subjected to an empirical collation using the program LISREL.8.20 (Jöreskog and Sörbom, 1993), applying the method of unweighted least squares. The results of this work provide empirical evidence to support the forwarded theory on the existing relationship between the personality variable of neuroticism and the coping strategies used by patients with chronic pain. It could be said that high levels of neuroticism become predictors of catastrophizing and seeking of social support , which are rather inefficient coping strategies.